(untitled) (Academicia Globe: Inderscience Research, 2024)
Initial of education the first in classes issues in solving students gathered now and the remainder to find circle , number one how many unity gain or to reduce circle total and joiners to find round , distinct to compare circle simple issues , differences and the reducer to find circle , difference and the parting one to find circle one how many in appearance to issues face they come Initial class students ability attention if we can , in them mathematician issues solve unformed , students simple and complicated issues complete read they can’t . In this matter to the students textual issues to solve in teaching to what main attention focus need about the word is conducted .